MONITORING ALIRAN ARUS PASANG SURUT AIR LAUT PADA PESISIR MUARA AIRKANTUNG BERBASIS ARDUINO - Bambang Supriyadi; Rindy Clarita; Yudhi Yudhi; Ocsirendi Ocsirendi (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2021)
Indonesia is an archipelagic country where each island is always surrounded by the ocean, as for the potential that can be used for renewable energy. The ocean tides are one of the natural phenomena that cause changes in sea level at certain times every day and will affect fishing activities and will affect the flow of the estuary, seeing the characteristics of Indonesian marine waters in general, especially in the Bangka area which is useful for human activities, especially those who related to the sea. Therefore we need a device that can monitor the flow of tidal currents of sea water. The purpose of making this device is to make a device that can measure and determine the current speed and sea level at the estuary of Air Kantung using an Arduino-based program. This method of measuring the speed of tidal currents is based on the principle of turbine rotation which is then read by the optocoupler sensor while the measurement of sea level is based on the principle of constant with ultrasonic sensor readings. The device can save the measurement results into a database which is then stored on the SD card data and can then be displayed on the LCD. The results of testing the optocoupler sensor at the current flow velocity with a comparison of the tool made with a tachometer obtained an average error of 1.17%. While testing the water level with an ultrasonic sensor by comparing the sensor value to the height size with an average error of 1.01%. The monitoring device for current flow and height on tidal flow tested 3 times with the results of measuring current velocity of 0.72% device error and 99.22% accuracy while measuring sea water level of 0.74% device error and 99,26%  accuracy, obtained from comparing monitoring devices with tachometers and meters.